Estrategia de rebranding para el posicionamiento de la empresa Agromaq en el cantón Penipe - Anguieta Gunsha, Sonia Patricia (2025)
The company Agromaq faces difficulties in its positioning and visibility in the agricultural market of Penipe due to the lack of a strong brand identity. This has limited their ability to differentiate themselves from the competition, a common problem in many agricultural companies in Ecuador. The main objective of the research was to design a rebranding strategy to improve Agromaq's positioning, in order to strengthen its visual identity, increase its market visibility, and connect more effectively with consumers. The methodology used was descriptive and action research, applying surveys, interviews, and direct observation to analyze consumer perceptions and branding practices in the competition. The results revealed that Agromaq lacks a coherent digital marketing strategy, which limits its reach. Although customers value their products, the company fails to effectively connect with its target audience due to a weak visual identity and inconsistent communication. The research contributes a structured rebranding model, highlighting the importance of coherent visual identity and the use of digital tools to improve competitiveness. It is concluded that comprehensive rebranding is essential to improve the positioning of the company Agromaq.